Here one moment - Moriarty, Liane (New York : Crown, 2024)
"The flight will be smooth, it will land safely. Everyone who gets on the plane will get off. But almost all of them will be forever changed. Because on this ordinary, short, domestic flight, something extraordinary happens. People learn how and when they are going to die. For some, their death is far in the future$1 (Bage 103!$1 (Band they laugh. But for six passengers, their predicted deaths are not far away at all. How do they know this? There were ostensibly more interesting people on the flight (the bride and groom, the jittery, possibly famous woman, the giant Hemsworth-esque guy who looks like an off-duty superhero, the frazzled, gorgeous flight attendant) but none would become as famous as (3z(BThe Death Lady.(3y (B-- Book jacket.s
Keywords: Air travel -- Fiction; Airplane occupants -- Fiction; Death -- Fiction; Fate and fatalism -- Fiction; Free will and determinism -- Fiction; Prophecies -- Fiction; Women psychics -- Fiction; Psychics -- Fiction; Thrillers (Fiction); Psychological fiction